Cargando…
A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n )
Autores principales: | , |
---|---|
Lenguaje: | eng |
Publicado: |
1968
|
Materias: | |
Acceso en línea: | https://dx.doi.org/10.1007/BF01380085 http://cds.cern.ch/record/846155 |
_version_ | 1780906854584418304 |
---|---|
author | Hepp, V Schleich, H |
author_facet | Hepp, V Schleich, H |
author_sort | Hepp, V |
collection | CERN |
id | cern-846155 |
institution | Organización Europea para la Investigación Nuclear |
language | eng |
publishDate | 1968 |
record_format | invenio |
spelling | cern-8461552019-09-30T06:29:59Zdoi:10.1007/BF01380085http://cds.cern.ch/record/846155engHepp, VSchleich, HA new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n )Particle Physics - Experimentoai:cds.cern.ch:8461551968 |
spellingShingle | Particle Physics - Experiment Hepp, V Schleich, H A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
title | A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
title_full | A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
title_fullStr | A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
title_full_unstemmed | A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
title_short | A new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
title_sort | new determination of the capture ratio : $\gamma$ 0 = $\sigma^{-}$ p -> $\sigma^{0}$ n / ( $\sigma^{-}$ p -> $\sigma^{0}$ n ) + ( $\sigma^{-}$ p -> $\lambda^{0}$ n ) |
topic | Particle Physics - Experiment |
url | https://dx.doi.org/10.1007/BF01380085 http://cds.cern.ch/record/846155 |
work_keys_str_mv | AT heppv anewdeterminationofthecaptureratiogamma0sigmapsigma0nsigmapsigma0nsigmaplambda0n AT schleichh anewdeterminationofthecaptureratiogamma0sigmapsigma0nsigmapsigma0nsigmaplambda0n AT heppv newdeterminationofthecaptureratiogamma0sigmapsigma0nsigmapsigma0nsigmaplambda0n AT schleichh newdeterminationofthecaptureratiogamma0sigmapsigma0nsigmapsigma0nsigmaplambda0n |